2013
DOI: 10.3233/cbm-130336
|View full text |Cite
|
Sign up to set email alerts
|

Complexin-2 (CPLX2) as a potential prognostic biomarker in human lung high grade neuroendocrine tumors

Abstract: The present study aimed to identify novel useful clinical biomarker of high grade lung neuroendocrine tumors (LNETs). Based on the results of QSTAR LC-MS/MS analysis, we selected complexin-2 (CPLX2) (upregulated 8.7-fold) as a potential biomarker in high grade human LNETs, and validated its expression immunohistochemically in comparison with non-small cell lung carcinomas (NSCLCs). CPLX2 was strongly positive in 16.3% of examined LNETs, but completely negative in all adjacent non-cancerous tissues and NSCLCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Previous studies have reported that CPLX2 plays a key role in maintaining normal neurological function, while its downregulation changes the neurotransmitter release that is sufficient to cause significant behavioral abnormalities, such as depression (10). Komatsu et al (14) reported that CPLX2 was strongly positive in 16.3% of large cell neuroendocrine carcinomas of the lung and small cell carcinomas of the lung, but completely negative in all adjacent non-cancerous tissues and in non-small cell lung carcinomas. They also demonstrated that positive CPLX2 expression was associated with lymph vessel invasion (P = 0.016), pathological stage (P = 0.031) and poor disease-specific survival (P = 0.004) in these patients.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Previous studies have reported that CPLX2 plays a key role in maintaining normal neurological function, while its downregulation changes the neurotransmitter release that is sufficient to cause significant behavioral abnormalities, such as depression (10). Komatsu et al (14) reported that CPLX2 was strongly positive in 16.3% of large cell neuroendocrine carcinomas of the lung and small cell carcinomas of the lung, but completely negative in all adjacent non-cancerous tissues and in non-small cell lung carcinomas. They also demonstrated that positive CPLX2 expression was associated with lymph vessel invasion (P = 0.016), pathological stage (P = 0.031) and poor disease-specific survival (P = 0.004) in these patients.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…After screening, we found 13 common genes in four groups of DEGs. Komatsu et al [26] studied clinical biomarkers of pulmonary neuroendocrine tumors (LNET) and found that CPLX2 was strongly positive in 16.3% of the examination groups. Importantly, positive CPLX2 expression is associated with lymphatic invasion, pathological staging, and adverse disease-specific survival in LNET patients.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, positive CPLX2 expression is associated with lymphatic invasion, pathological staging, and adverse disease-specific survival in LNET patients. It was finally concluded that CPLX2 is a novel clinical biomarker for LNET [26]. In the study of breast cancer diagnostic markers, Fu et al [27] found that changes in gene expression such as DPEP1 may lead to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a positive role in Ca 2Ăľ -triggered exocytosis by facilitating vesicle priming [27]. Complexin-2 is regarded as a potential prognostic biomarker in human lung highgrade neuroendocrine tumors [28].…”
Section: Quantitative Proteomic Analyses Of A549 Treated With Lip Andmentioning
confidence: 99%